PaMiNI-Derived Co-Activation Patterns Indicate Differential Hierarchical Levels for Two Ventral Visual Areas of the Fusiform Gyrus - Caspers, J.; Eickhoff, S. B.; Amunts, K.; Antoch, G.; Zilles, K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To investigate the distribution of co-activation patterns of the recently identified ventral visual areas FG1 and FG2 of the posterior fusiform gyrus using the novel meta-analytic approach PaMiNI (Pattern Mining in NeuroImaging).Materials and Methods: All neuroimaging experiments reporting activation foci within FG1 or FG2 were retrieved from the BrainMap database. The stereotaxic activation foci in standard reference space were analyzed with PaMiNI. Here, Gaussian mixture modeling was applied to the stereotaxic coordinates of all foci to identify the underlying brain regions of each dataset. Then, association analysis was performed to reveal frequent co-activations across the modeled brain regions.Results: Co-activation patterns of FG1 were mainly found within the visual system, i. e. in early visual areas, and were symmetrically distributed across both hemispheres. FG2 features several extra-visual co-activations, mainly to inferior frontal, premotor and parietal regions. Furthermore, the co-activations of FG2 showed clear lateralization to the left FG2.Conclusion: FG1 shows characteristics of an intermediate visual area between the early ventral visual cortex and the category-specific higher-order areas. Co-activation patterns of FG2 indicate that FG2 is a higher-order visual area that probably corresponds to the posterior fusiform face area and partly the visual word-form area.Key points• Co-activation patterns of areas FG1 and FG2 were analyzed with PaMiNI.• FG1 features mainly symmetric co-activations to areas of the visual system.• FG2 shows several extra-visual co-activations, which are left-lateralized.• FG1 corresponds to a hierarchically intermediate, FG2 to a higher-order visual area.• The PaMiNI approach is extended to seed-specific mapping of co-activation patterns.Citation Format:• Caspers J, Eickhoff SB, Amunts K et al. PaMiNI-Derived Co-Activation Patterns Indicate Differential Hierarchical Levels for Two Ventral Visual Areas of the Fusiform Gyrus. Fortschr Röntgenstr 2015; 187: 892 – 898
Keywords: pattern mining in neuroimaging; brainmap database; coordinate-based meta-analysis; ventral visual cortex; fusiform face area; visual word-form area